Some Photosynthetic Indicators of Soybean Varieties - Fozilov Sherzod Musurmonovich; Xandalova Sharofat Komiljonovna; Samadov Amirxon Qudrat o'g'li (Zien Journals, 2022)
In this article given results of bioecological and morphological features klof the perspective varieties of soybean in the conditions of Surkhandarya region. Certain photosynthetic index (maintenances of pigments, productivity of photosynthesis) of different sorts of soy.
Keywords: sorts of soy; photosynthesis; pigment; productivity of photosynthesis